Daniel Sempere's Ambitions in Carlos Ruiz Zafon's The Shadow of The Wind - Noor, Zachry; Cahyaning Rahayu, Anik (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2024)
This research discusses about Daniel’s ambitions in Carlos Ruiz Zafon’s The Shadow of the Wind. This research aims to explain and describe Daniel’s journey in achieving his ambitions. This research uses the novel, The Shadow of the Wind as the source of the data. This research uses a psychological approach and sanguine temperament characteristics from Ludwig Klages’ in psychological theory of character. The theory and approach used as a guide to analyse the data, describes and reveals the main character’s ambitions in the story. Descriptive qualitative method is used in this research. The results of this research shows that Daniel has three ambitions, becoming a writer, finding out Julian Carax, and saving Beatriz. Daniel’s ambitions are based on his connection with other people and the desire to help others. Daniel struggles to reach his ambitions, and faces a lot of challenges and hinderances. However, Daniel still has a strong courage, desire, confidence and optimism which makes him successful to reach his ambitions. Daniel finally achieves his ambitions to find out Julian Carax and to be with Beatriz Aguilar.